Association of hypocalcemia with other iron overload complicationsin Beta thalassemia major patients - Farooq, Nazish (ADVANCES IN BASIC MEDICAL SCIENCES, 2019)
Background: Multi-transfused Î²-thalassaemia major patients, may develop severe endocrine complications due to iron overload. The anterior pituitary is particularly sensitive to iron overload which disrupts hormonal secretion resulting in hypogonadism, short stature, acquired hypothyroidism and hypoparathyroidism. Cardiac complications and diabetes mellitus are also common in thalassaemic patients. Materials and methods: This cross sectional study was conducted at Fatimid foundation Peshawar from June 2015 to August 2015. One hundred diagnosed Î²-thalassemia major patients were enrolled and blood samples were drawn to determine serum calcium and phosphorus levels using Microlab 200. Heights of patients were measured in centimeters. Levels of thyroid stimulating hormone (TSH), thyroxin (free T4), random blood glucose, ECG, X-ray and echo- cardiography were all noted and positive cases of short stature, hypothyroidism, diabetes mellitus and cardiac dysfunction were recorded and their association with hypocalcemia was observed. Data was analysed using SPSS. Results: Short stature was observed in 39 hypocalcemics, hypothyroidism in 7, cardiac dysfunction in 5 and 4 patients had hypocalcemia along with diabetes. Conclusion: Hypocalcemia is most frequently associated with short stature and least frequently with diabetes mellitus.